Peran Literasi Keluarga dalam Meningkatkan Kemampuan Membaca Anak Usia Dini Studi Kasus Kelurahan Panaikang Kota Makassar - Ahmad, Ahmad (Faculty of Tarbiyah and Teacher Training, 2025)
This study aims to analyze the role of family literacy in improving early childhood reading skills in Panaikang Village, Makassar City. This research method uses a qualitative approach with a case study in Panaikang Village, which involves in-depth interviews with parents and local community leaders. Data were also obtained through observations of literacy activities carried out at home and analysis of the socio-economic conditions of families. The study results indicate that although there is great potential for families to play an active role in improving children's reading skills, various factors such as limited time, resources, and parental knowledge hinder these efforts. This study suggests the importance of empowering parents and families through literacy training programs, providing easily accessible reading materials, and increasing awareness of the importance of early childhood literacy. The results of this study can contribute to designing more effective education policies and family empowerment programs in Panaikang Village, as well as other areas with similar challenges.